Professional Self-Determination in the Context of Continuing Education - Dubrovina, I.V. (Bulletin of Practical Psychology of Education, 2024)
The article is devoted to the problem of professional self-determination of schoolchildren in the field of pedagogical activity. It is shown that this self-determination occurs in the process of lifelong education, which at each age stage creates conditions for the development of professional orientation of schoolchildren. The stage of pre-professional (pre-university) pedagogical education includes preschool childhood, takes place at school, ends with the choice of a profession, its main task is to develop interest in the teaching profession, identify and form pedagogical abilities. The stage of professional education helps the student to accept the requirements of the profession. The stages of mentoring and postgraduate education allow the teacher to find deeper meanings in the field of professional activity. The positive role of creating pedagogical classes at school is noted in order to provide students with more directed psychological preparation for choosing a teaching profession and more meaningful admission to a pedagogical university. Some proposals have been formulated for a program that ensures the educational process in teaching classes. Статья посвящена проблеме профессионального самоопределения школьников в области педагогической деятельности. Показано, что это самоопределение происходит в процессе непрерывного образования, которое на каждом возрастном этапе создает условия для развития профессиональной ориентации школьников. Этап допрофессионального (довузовского) педагогического образования включает дошкольное детство, проходит в школе, завершается выбором профессии. Главная его задача - развитие интереса к профессии учителя, выявление и формирование педагогических способностей. Этап профессионального образования помогает студенту принять требования профессии. Этапы наставничества и послевузовского образования позволяют педагогу находить более глубокие смыслы в сфере профессиональной деятельности. Отмечается позитивная роль создания в школе педагогических классов с целью более направленной психологической подготовки учащихся к выбору профессии учителя и более осмысленного поступления в педагогический вуз. Сформулированы некоторые предложения к программе, обеспечивающей учебный процесс в педагогических классах.